The role of surface disinfection in infection prevention - Gebel, Jürgen; Exner, Martin; French, Gary; Chartier, Yves; Christiansen, Bärbel; Gemein, Stefanie; Goroncy-Bermes, Peter; Hartemann, Philippe; Heudorf, Ursel; Kramer, Axel; Maillard, Jean-Yves; Oltmanns, Peter; et al. (German Medical Science GMS Publishing House, 2013)
[english] Background: The Rudolf Schuelke Foundation addresses topics related to hygiene, infection prevention and public health. In this context a panel of scientists from various European countries discussed "The Role of Surface Disinfection in Infection Prevention". The most important findings and conclusions of this meeting are summarised in the present consensus paper.Aim: Although the relevance of surface disinfection is increasingly being accepted, there are still a number of issues which remain controversial. In particular, the following topics were addressed: Transferral of microbes from surface to patients as a cause of infection, requirements for surface disinfectants, biocidal resistance and toxicity, future challenges.Methods and findings: After discussion and review of current scientific literature the authors agreed that contaminated surfaces contribute to the transmission of pathogens and may thus pose an infection hazard. Targeted surface disinfection based on a risk profile is seen as an indispensable constituent in a multibarrier approach of universal infection control precautions. Resistance and cross-resistance depend on the disinfectant agent as well as on the microbial species. Prudent implementation of surface disinfection regimens tested to be effective can prevent or minimize adverse effects.Conclusions: Disinfection must be viewed as a holistic process. There is a need for defining standard principles for cleaning and disinfection, for ensuring compliance with these principles by measures such as written standard operating procedures, adequate training and suitable audit systems. Also, test procedures must be set up in order to demonstrate the efficacy of disinfectants including new application methods such as pre-soaked wipes for surface disinfection.